Effect of different methods of planting and spacing on growth and yield of cardamom (Elettaria cardamomum Maton) - KRISHNAKUMAR, M R SUDHARSHAN, SIDDAGANGAIAH SIDDAGANGAIAH, V (Journal of Spices and Aromatic Crops, 1998)
Experiments cop.ducted at Sakaleshpur (Karnataka, India) to study the effect of different methods of planting and spacing on growth and yield of cardamom (Elettaria cardamomum) indicated that trench method of planting (60 cm x 30 cm) at 2 m x 1 m spacing resulted in significantly better growth and yield.